Manajemen Perilaku Organisasi dalam Meningkatkan Tenaga Pendidik yang Kompeten di SMANegeri 2 Sepauk Kabupaten Sintang - Illuminata Novianti; Luhur Wicaksono; Marinu Waruwu (Journal on Education, 2024)
This study examines the implementation of organizational behavior management (OBM) to enhance the competency of educators at SMA Negeri 2 Sepauk, Sintang, Kalimantan Barat. The research highlights the critical role of OBM in improving teacher performance through effective leadership, communication, and the creation of a collaborative school culture. Using a mixed-method approach combining case studies and literature reviews, this study explores the barriers to OBM implementation, the relationship between organizational behavior and teacher competence, and the development of a tailored OBM model. Key findings indicate that effective OBM improves pedagogical, professional, social, and personal competencies of teachers. However, challenges such as limited resources, resistance to change, and inadequate access to technology hinder its full implementation. A proposed integrative OBM model focuses on leadership, inclusive culture, training, technology management, and performance evaluation. This model aligns with the needs of SMA Negeri 2 Sepauk to develop an adaptive and innovative educational ecosystem. The findings provide practical recommendations for enhancing organizational behavior management in schools, contributing to the broader discourse on improving teacher competencies in Indonesia.